PROSES BERPIKIR SISWA YANG MENGIKUTI EKSTRAKULIKULER BRIDGE PADA PENYELESAIAN SOAL CERITA TEORI PELUANG BERDASARKAN RANAH KOGNITIF TAKSONOMI BLOOM REVISI - Hendra Laksana, Priyo Dwi; Setiawan, Totp' Bara; Setiawani, Susi (Department of Mathematics Education , University of Jember, 2017)
Abstrak. This research aims to discover Students’ thinking process who follow extracurricular bridge in Senior High School 1 Arjasa in solving mathematical probability word problems, then describe and determine students’ thinking process. Intrument which were used in this research are mathematical word problems test and interview guidelines with indicators of revised bloom’s taxonomy cognitive domain. Students answered the problems then analyzed, if indicators did not appear in students answers then the interview is done according to the guideline. Based on the result of this research students who follow the extracurricular bridge belong to the level of thinking process C2 (understand) especially interpreting and explaining and belong to the level of thinking process C3 (apply) especially executing. Keywords: Bloom's Taxonomy Revised, bridge, thingking process